A produtividade dos sujeitos com deficiência na articulação da educação profissional e tecnológica com a inclusão - Turchiello, Priscila (2017)
This Thesis has as its purpose to understand how the technological and professional education invests in the constitution of productive individuals in the neoliberal rationality of inclusive matrix. Inspired by the thoughts of Michel Foucault and in the Foucaultian studies in education, it has been intended to develop an exercise of analysis of the technological and professional education with the Contemporaneity, from the analytical tool government and from the transversal, biopolitic, neoliberalism, human capital, and productivity notions. The chosen documents to embody the materiality refer to public politics, materials from programs of Governs and productions that are published with the purpose of presenting actions and principles that orientate the technological and professional education and the inclusion, and were organized into three groups: the first in which are the documents I understand that integrate the politic of technological and professional education; in the second the documents that turn to the productive inclusion of people with disability in the present time have been disposed; the third, destinated to the documents of programs of Govern that constitute a network of partnerships driven to the insertion of people with disability in the job Market. From the analytical enterprise carried out, it was possible to understand that the technological and professional education ends up reconfiguring itself to meet the necessities of investment in human capital in the contemporary context. Articulated, the technological and professional education work as technologies of government of the behavior of the people on the heels of the neoliberal rationality, investing on the development of the abilities and skills needed for the productive inclusion in the job games. On what refers to the people with disabilities, the deployments and changes of emphasis in the inclusion in the Contemporaneity generate the necessity that the persons develop an individual capital that allows them to migrate from school to other educational and social contexts, aiming their inclusion and maintenance in this condition. In the operationalization of the technological and professional education with the inclusion, I have visualized the operation of integration practices, verticalization and flexibilization of the routes of professional formation aiming to invest in the constitution of entepreunal and self-manager individuals, as specific actions are put in operation from the constitution of partnerships that objective to potentialize the inclusion of people with disabilities in the job market. In this way, the articulation between the technological and professional education and the inclusion invests in the productivity of the individuals with disabilities in a way of developing the conditions of competition for their entrance and continuity in the neoliberal economic game.